Transformasi Pertanian Dalam Ruangan: Hidroponik Cerdas Berbasis IoT : Indoor Farming Transformation: IoT-Based Smart Hydroponics - Caniago, Deosa Putra; Masril, M Abrar (AI Society & STMIK Indonesia, 2023)
The growth of technology has had a significant impact on the agricultural sector, including the method of hydroponic cultivation. According to the Basic Health Research (Riskesdas) conducted by the Ministry of Health, 90% of the Indonesian population lacks sufficient vegetable consumption. The World Health Organization (WHO) recommends a daily vegetable intake of around 400 grams for adults, which can be fulfilled through indoor hydroponic gardens. However, hydroponic cultivation requires intensive monitoring and control, posing a challenge for busy urban communities. Therefore, one solution to address the challenges in hydroponic farming is leveraging Internet of Things (IoT) technology and utilizing Real-time Clock (RTC) to create a Smart Indoor Hydroponic Garden system that enables real-time control of water pH and room temperature using temperature sensors and water quality sensors. This system can be utilized by urban individuals who lack access to open land, allowing them to meet their daily vegetable needs directly from home.